43rd International Conference on Organizational Science Development: Green and Digital Transition – Challenge or Opportunity: Conference Proceedings (University of Maribor Press, 2024)
The 43rd International Scientific Conference on the Development of Organisational Science was held in Portorož from the 20th to the 22nd of March 2024. The main aim of the conference was to promote the importance of knowledge in the context of green and digital transtition of organizations, through academic and scientific debates and professional developments from the economic and non-economic worlds. The conference, which was held under the umbrella title " Green and Digital Transition - Challenge or Opportunity", aimed to highlight the importance of the green and digital transition for the successful achievement of organisational objectives and the appropriate overcoming of societal challenges. The objectives pursued in this context are related to the natural dimensions on the one hand, and to stimulating the economy through green technology, sustainable development and pollution reduction on the other. The green and digital transition is also an opportunity for organisations to make changes towards overarching environmental challenges. It is undoubtedly more important than ever to take decisions that generate synergies between innovation, different sciences, and applied approaches, and to promote changes in business models that will lead to a sustainable and socially responsible development environment. In Portorož, we have reconnected opinions, views, and scientific and professional debates that will stimulate all of us to act in the future, both in organizations and in society at large.